Adaptive Control Strategies for the Production of Thermo-mechanically Tailored Products - Clobes, Jörg (Kassel University Press GmbH_Legacy, 2014)
Within the rapidly growing field of hot sheet metal forming and metal bulk forming the demand arises for fully three-dimensionally tailored properties at the microstructural level, nevertheless, reaching a predefined geometry with such tailored properties puts high requirements on the control mechanisms utilized in the process chain for combined heating, metal forming, and cooling processes. Therefore, the underlying control architecture needs to be freely configurable with respect to a predefined database being extendible to new geometries, microstructural distributions, and materials. The combined control of locally and temporally differential thermo-mechanical effects during the process flow needs to be based on an adaptive algorithm adjusting the process flow in real-time according to predefined parameters delivered by the aforementioned material, geometry, and microstructure property database. The interplay between measurement techniques and adaptive control processes for hot metal forming of functionally graded materials is to be investigated in order to achieve the predefined fully three-dimensional microstructure in complex geometries and optimize the process cycle time in a freely configurable control architecture being customizable to new requirements and materials, resulting in a precision manufacturing process. The emphasis within the given thesis will be on adaptive control strategies embedded within a flexible control architecture for an innovative thermo-mechanical production process embracing induction heating to predefined spatial and temporal temperature distributions, transfer, and combined metal forming as well as heat extraction processes. The flexible control architecture assures an invariant quality for the highly dynamic processes and, moreover, yields extendibility to new materials, geometries, and microstructural distributions.